Risk factors of stunting for 12-36 month old children in Dasan Agung Public Health Centre, Mataram, West Nusa Tenggara Province - Imtihanatun Najahah; Kadek Tresna Adhi; Gede Ngurah Indraguna Pinatih (Public Health and Preventive Medicine Archive, 2013)
A very high stunting prevalence (37.17 %) was reported in Mataram City, West Nusa Tenggara. Dasan Agung Public Health Centre localed at the centre of Mataram City reports the highest stunting prevalence (27.78%) in children under 5 year of age. The study design was a cross sectional, using a sample of 158 children aged 12-36 month. The dependent variable was 12-36 month old children displaying stunting and the independent variables were socio-economic status, mother’s height, maternal age, mother’s level of education, ANC clinic visit frequency and quality of care, birth weight, exclusive breastfeeding, complementary feeding, birth order and main caregiver choice. Data was collected through interviews and anthropometric measurement. The instruments used in collecting the data were RISKEDAS and SUSENAS I modification questionnaires, microtoise and infantometer. Data analysis was conducted in stages that included univariate, bivariate (chi-square) and multivariate (logistic regression). A high prevalence of stunting (48.1%) was evident. There were six variables in the bivariate test results impacted upon of association. These were socio-economic status OR=2.83 (95%CI: 1.35-5.94), mother’s height OR=3.37 (95%CI: 1.69-6.72), ANC clinic visit frequency and quality of care OR=2.3 (95%CI: 1.21-4.36), birth weight OR=20.47 (95%CI: 1.16-354.25), exclusive breastfeeding OR=4.94 (95%CI: 2.51-9.74) and complementary feeding OR=6.38 (95%CI: 3.18-12.78). The variables of maternal age, mother’s level of education, birth order and main caregiver choice were not influencing factors. In the multivariate analysis, the dominant variables increasing risk factors was complementary feeding giving OR=7.4 (95%CI: 1.54-34.97), mother’s height OR=2.9 (95%CI: 1.27-6.42) and ANC clinic visit frequency and quality of care OR=2.4 (95%CI: 1.09-5.19). It is recommended that there be efforts to improve the nutrition intake of young girls, women of productive age, pregnant women and children under five years old.